ARRY-334543 reverses multidrug resistance by antagonizing the activity of ATP-binding cassette subfamily G member 2 - Wang, De-Shen (2014)
BACKGROUND: ARRY-334543 is a small molecule inhibitor of ErbB1 and ErbB2 tyrosine kinases. We conducted this study to determine whether ARRY-334543 can enhance the efficacy of conventional anticancer drugs through interaction with ABC transporters. METHODS: Lung cancer cell line NCI-H460 and its ABCG2-overexpressing NCI-H460/MX20, as well as the ABCG2-, ABCB1-, and ABCC10-overexpressing transfected cell lines were used for the reversal study. RESULTS: Our results demonstrate that ARRY-334543 (1.0 μM) significantly reversed ABCG2-mediated multidrug resistance (MDR) by directly inhibiting the drug efflux function of ABCG2, resulting in the elevated intracellular accumulation of chemotherapeutic drugs in the ABCG2-overexpressing cell lines. In addition, in isolated membranes, ARRY-334543 stimulated ATPase activity and inhibited photolabeling of ABCG2 with [(125)I]-iodoarylazidoprazosin in a concentration-dependent manner indicating that this drug directly interacts at the drug-binding pocket of this transporter. ARRY-334543 (1.0 μM) only slightly reversed ABCB1- and partially reversed ABCC10-mediated MDR suggesting that it exhibits high affinity towards ABCG2. Moreover, homology modeling predicted the binding conformation of ARRY-334543 at Arg482 centroid-based grid of ABCG2. However, ARRY-334543 at reversal concentration did not affect the expression level of ABCG2, AKT and ERK1/2 and regulate the re-localization of ABCG2. CONCLUSION: We conclude that ARRY-334543 significantly reverses drug resistance mediated by ABCG2.